Pengaruh Terapi Akupresur terhadap Mual, Muntah, dan Kualitas Hidup Anak dengan Leukemia - Raihan, Agus Tiar Bintang; Nurhayati, Siti (Maternal & Neonatal Health Journal, 2025)
Leukemia, commonly known as blood cancer, is a type of blood cancer that occurs when white blood cells outside normal limits multiply rapidly in the bone marrow. This process involves white blood cells, an important part of the immune system that fights infections. Leukemia occurs when an abnormality causes the bone marrow to produce more mature white blood cells (leukemia cells). To determine the effect of acupressure therapy on vomiting nausea and the quality of life of children with leukemia. The method used is review literature by searching articles through Google Scholar and PubMed databases. There are 3 articles that meet inclusion and exclusion criteria. Results show that acupressure therapy can significantly lower vomiting nausea and improve the quality of life. Conclusion: Acupressur therapy has proven effective as complementary therapy to lower vomiting nausea and improve the quality of life for leukemia children.